Restaurování a konzervace uměleckých děl na papírové podložce - Kašparová, Věra (Univerzita Pardubice, 2014)
The Restoration of Artworks on Paper Support is relatively a new area and crux of the problem is how to technologically combine the restoration of paper support and paint layer. This thesis is mainly about conception of conservation and restoration of artworks on paper support. The theoretical part deals with the basic terminology in area of restoration and conservation, as well as development of the restoration practice and views on the completion of missing parts and examples of conceptions of restoration of artworks on paper support. The thesis includes also detail description of exemplary restoration processes on selected works and it is emphasizing different approaches to restoration practice. The restoration process was executed on paintings on paper supports with religious themes which were found in small church in Prackov in desolated state and all the themes were painted by two local painters, Jan Šilhán and unknown author, in 19th/20th century. Finally 21 different types of conceptions were presented and described in detail in the thesis (3 conservation treatments, 3 partial restoration treatments and 15 complete restoration treatments).
The Conception of Conservation and Restoration of Artworks on Paper Support